Respuestas
Respuesta dada por:
31
Desarrollo:
a) Solución:
![-2(x+y)=-2(4) -2(x+y)=-2(4)](https://tex.z-dn.net/?f=-2%28x%2By%29%3D-2%284%29)
![2x+4y=10 2x+4y=10](https://tex.z-dn.net/?f=2x%2B4y%3D10)
Nos da:
![-2x-2y=-8 -2x-2y=-8](https://tex.z-dn.net/?f=-2x-2y%3D-8)
![2x+4y=10
2x+4y=10](https://tex.z-dn.net/?f=2x%2B4y%3D10%0A)
la suma sera:
![-2x+2x-2y+4y=-8+10 -2x+2x-2y+4y=-8+10](https://tex.z-dn.net/?f=-2x%2B2x-2y%2B4y%3D-8%2B10)
![2y=2 2y=2](https://tex.z-dn.net/?f=2y%3D2)
![y=1 y=1](https://tex.z-dn.net/?f=y%3D1)
Remplazamos:
![x+y=4 x+y=4](https://tex.z-dn.net/?f=x%2By%3D4)
![x+1=4 x+1=4](https://tex.z-dn.net/?f=x%2B1%3D4)
![x=3 x=3](https://tex.z-dn.net/?f=x%3D3)
b) solución:
![-2(x-4y)=-2(2) -2(x-4y)=-2(2)](https://tex.z-dn.net/?f=-2%28x-4y%29%3D-2%282%29)
![2x-5y=7 2x-5y=7](https://tex.z-dn.net/?f=2x-5y%3D7)
Nos da:
![-2x+8y=-4 -2x+8y=-4](https://tex.z-dn.net/?f=-2x%2B8y%3D-4)
![2x-5y=7 2x-5y=7](https://tex.z-dn.net/?f=2x-5y%3D7)
La suma sera:
![-2x+2x+8y-5y=-4+7 -2x+2x+8y-5y=-4+7](https://tex.z-dn.net/?f=-2x%2B2x%2B8y-5y%3D-4%2B7)
![3y=3 3y=3](https://tex.z-dn.net/?f=3y%3D3)
![y=1 y=1](https://tex.z-dn.net/?f=y%3D1)
Remplazamos:
![x-4y=2 x-4y=2](https://tex.z-dn.net/?f=x-4y%3D2)
![x-4=2 x-4=2](https://tex.z-dn.net/?f=x-4%3D2)
![x=6 x=6](https://tex.z-dn.net/?f=x%3D6)
Un gusto :D
a) Solución:
Nos da:
la suma sera:
Remplazamos:
b) solución:
Nos da:
La suma sera:
Remplazamos:
Un gusto :D
stylebooks:
otra pregunta
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años